Perioperative effects of oral midazolam premedication in children undergoing skin laser treatment: a double-blinded randomized placebo-controlled trial - Shoroghi,Mehrdad (2011)
PURPOSE: To investigate and compare the efficacy of oral midazolam with two different dosages in orange juice on perioperative hemodynamics and behavioral changes in children who underwent skin laser treatment in an academic educational Hospital. METHODS: Ninety children, candidates for skin laser treatment were randomly assigned to 1 of 3 groups of 30 each: the placebo group received 0.1 ml/kg orange flavored juice, group 2 and 3 receiving 0.5 and 1 mg/kg of injectable midazolam mixed with an equal volume of orange juice, respectively. The main outcome measures included the mask acceptance, patients' behavioral scales and postoperative events. RESULTS: There were no significant differences in heart rate, respiratory rate, and systolic blood pressure among the three groups. However, arterial oxygen saturation was significantly reduced in those given 1 mg.kg-1 midazolam. The median scores of anxiety, separation from parent, preparing an intravenous line, acceptance of the oxygen mask, good sedation, crying reduction and consciousness level were better in midazolam group. Postoperative agitation and re-crying were also more frequent in placebo receivers. Those given 1 mg.kg-1 midazolam were significantly more optimal for sedation, crying, consciousness, preparing an intravenous line, and postoperative re-crying compared with 0.5 mg.kg-1 midazolam receivers. CONCLUSION: As a preanaesthetic medication, the 1 mg.kg-1 dose of orally given midazolam especially in a volume of orange juice and can optimize the children's behavior during skin laser treatment with no serious adverse effects, enhancing their parents' satisfactions about the sedative protocol.